To solve the equation, we will complete each step:
Step 1: Subtract 11/3 from both sides
5/3x + 11/3 - 11/3 = -4/3 - 11/3
5/3x = -15/3
Step 2: Simplify both sides of the equation
5/3x = -5
Step 3: Multiply both sides by 3/5 (the reciprocal of 5/3) to isolate x
(3/5)(5/3x) = (3/5)(-5)
(1)(x) = -3
Therefore, the solution is x = -3.
The equation 5/3x + 11/3 = - 4/3 is solved as follows. Supply the correct numbers to complete the solution.
5/3x + 11/3 = -4/3
5/3x=__subtract 11/3 from both sides
x =__ multiply both sides by 3/5, the resiprocal of 5/3
1 answer